2005
DOI: 10.1002/ptr.1683
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Mornidae Radix extracts on experimental osteoporosis in sciatic neurectomized mice

Abstract: The preventive and therapeutic effects of aqueous extracts of Mornidae Radix (MR) were observed in sciatic neurectomized mice, a disused osteoporotic model. The right hind limbs of 80 mice were neurectomized and 20 mice were sham-operated and served as a sham control. Then 50, 100 and 200 mg/kg of MR extracts were dosed 3 days after neurectomy for 6 weeks in the prevention study and were dosed 2 weeks after neurectomy for 12 weeks for the therapeutic study. After dosing with the MR extracts, the thickness of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…In addition, the root extract also significantly and dose-dependently suppressed the decrease in histomorphometric parameters of the tibia such as volume, length and thickness of trabecular bone and thickness of cortical bone in ovariectomized rats. They may act as both a suppressor of bone resorption and an enhancer of bone formation in vivo and may have some favorable effects for preventing and treating the osteoporosis induced by sciatic neurectomy and ovariectomy [67, 68]. The polysaccharides from Morinda officinalis can exert an increase in bone mineral density and mineral element concentration, a decrease in serum cytokines level in OVX rats [69].…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the root extract also significantly and dose-dependently suppressed the decrease in histomorphometric parameters of the tibia such as volume, length and thickness of trabecular bone and thickness of cortical bone in ovariectomized rats. They may act as both a suppressor of bone resorption and an enhancer of bone formation in vivo and may have some favorable effects for preventing and treating the osteoporosis induced by sciatic neurectomy and ovariectomy [67, 68]. The polysaccharides from Morinda officinalis can exert an increase in bone mineral density and mineral element concentration, a decrease in serum cytokines level in OVX rats [69].…”
Section: Resultsmentioning
confidence: 99%
“…There are two major therapeutic strategies for osteoporosis treatment: reducing bone turnover and increasing mineral deposition on bones. As bone-turnover reduction compounds, polysaccharides from morinda officinalis has been prescribed to osteoporosis patients and have proved to be safe with few side effects [17,18]. MOP stimulates osteoblastic bone formation, markedly increases bone mass, prevents vertebral fractures, and has been developed to treat osteoporosis [19,20].…”
Section: Discussionmentioning
confidence: 99%
“…And in Morinda officinalis, there are various anthraquinones constituents including rubiadin, rubiadin-1-methyl, 1-hydroxyanthraquinone and so on (Yang et al, 1992), and it have been reported that aqueous extract of Morinda officinalis could evidently suppress the bone loss in osteoporotic mice induced by sciatic neurectomy surgery (Seo et al, 2005). Therefore, rubiadin-1-methyl ether and its derivatives may be the antiosteoporotic constituents in Morinda officinalis.…”
Section: Tablementioning
confidence: 96%